Evaluation Of The Financial Performance Of Bank Syariah Indonesia Using The Camel Method - Fi Amanillah, Izzatul Maula; Ghofur, Abd.; Maulidiyah, Nailin Nikmatul (LPPM ISNJ Bengkalis, 2024)
Financial performance is essential for banking institutions. Good financial performance can increase public confidence in investing capital and applying for financing to banks. This research aims to evaluate the financial performance of Bank Syariah Indonesia after the merger. This research uses a descriptive quantitative approach with data sources in the form of secondary data. The data collection technique uses documentation from Bank Syariah Indonesia's financial reports for 2021-2023. The data analysis technique uses the CAMEL method: capital, assets, management, earnings and liquidity. The research results show that the capital aspect from 2021 to 2023 falls within the excellent criteria. The asset aspect from 2021 to 2023 is included in the excellent criteria. The management aspect from 2021 to 2023 falls into the suitable criteria. The earnings aspect from 2021 to 2023 is included in the excellent criteria. The excellent criteria include the liquidity aspect from 2021 to 2023. Bank Syariah Indonesia's financial performance after the merger from 2021 to 2023 is healthy. This research can be used as reference material for evaluating Bank Syariah Indonesia and improving its financial performance in the future. Then, it can also be a reference for stakeholders in making decisions.